Mechanical alloying produces grain boundary segregation in Fe–Mg powders. (15th April 2020) - Amram, Dor; Schuh, Christopher A.
Abstract: Although mechanical alloying can force immiscible elements into homogeneous solid solution due to its chemically "randomizing" nature, as microstructure design of powder-processed alloys advances, other alloy configurations are also sought. Here we study ball milling of Fe–Mg alloys and obtain a heterogeneous nanostructure, with grain boundaries decorated by solute even after reaching complete supersaturation and a steady-state grain size. Such nanocrystalline powders having grain boundary segregation in the as-milled state are particularly useful for thermal stability against grain growth. The high diffusivity of Mg is thought to shift the competition between ballistic mixing and equilibration, permitting such a structure to form. Graphical abstract: Image, graphical abstract